Macroprudential policy and the role of institutional investors in housing markets - Manuel A. Mu\~noz (European Central Bank (ECB), 2020)
Since the onset of the Global Financial Crisis, the presence of institutional investors in housing markets has steadily increased over time. Real estate funds (REIFs) and other housing investment …rms leverage large-scale buy-to-rent investments in real estate assets that enable them to set prices in rental housing markets. A signi…cant fraction of this funding is being provided in the form of non-bank lending (i.e., lending that is not subject to regulatory LTV limits). I develop a quantitative two-sector DSGE model that incorporates the main features of the real estate fund industry in the current context to study the effectiveness of dynamic LTV ratios as a macroprudential tool. Despite the comparatively low fraction of total property and debt held by REIFs, optimized LTV rules limiting the borrowing capacity of such funds are more effective in smoothing property prices, credit and business cycles than those a¤ecting (indebted) households’borrowing limit. This …nding is remarkably robust across alternative calibrations (of key parameters) and speci…cations of the model. The underlying reason behind such an important and unexpectedly robust …finding relates to the strong interconnectedness of REIFs with various sectors of the economy.
Keywords: E44; G23; G28; 330; rental housing; real estate funds; loan-to-value ratios; leverage